2013
DOI: 10.1007/s13280-013-0464-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sustainable Utilization of Land Resources in China: Problems, Policies, and Practices

Abstract: China's economy is growing explosively with double-digit rates of growth. However, behind the scenes of this economic miracle, a dark underbelly exists. The potential impact of the unsustainable use of land resources is increasing. Each parcel of land has a stationary geographic location, while its utilization is optional. The readjustment and optimization of land use patterns ought to be encouraged. Spatial reconstruction refers to the combination of various land elements, which can promote the rational and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Considering the issues of climate change, studies should focus on identifying relevant driving forces of low carbon technology innovation and their interaction in the construction industry. Also, Hong et al (2014) explored the re-adjustment and optimization of land-use patterns and came to a conclusion that pursuing sustainable development and building an ecological civilization are imperative for the future of the construction industry.…”
Section: Study Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the issues of climate change, studies should focus on identifying relevant driving forces of low carbon technology innovation and their interaction in the construction industry. Also, Hong et al (2014) explored the re-adjustment and optimization of land-use patterns and came to a conclusion that pursuing sustainable development and building an ecological civilization are imperative for the future of the construction industry.…”
Section: Study Focusmentioning
confidence: 99%
“…Author(s) Contribution Fernandez (2007) Examined the consumption of material resources and concluded that there is a need to formulate strategies for a circular economy that include a resourceefficient Tam et al (2007) The authors proposed that the values of water absorption of the pre-treated recycled aggregate in construction have to be significantly reduced with improved mechanical properties to be recyclable Lemougna et al (2011) The authors concluded that laterite can contribute to solving the problem of affordable housing and providing environmentally-friendly Yuan et al (2011) In an attempt to evaluate the efficiency of recycling construction and demolition waste, the study demonstrated that the close-loop recycling option is better than the open-loop recycling option for construction and demolition waste Huang et al (2013) The outcome of the study indicated effective material reuse influences materials demand and related CO 2 emissions for new buildings construction Atolagbe and Fadamiro (2014) The authors proposed five major factors of sustainability to justify the use of sustainable material of both housing and environmental developments Dean et al (2014) The authors concluded that an expanded business operations model (EBOM) is essential assessing an a company's goal of environmental stewardship He et al (2014) While assessing the overall context of energy efficiency in rural China, the authors concluded that a new theoretical framework is required to assist decision-makers in achieving energy efficiency Hong et al (2014) Pursuing sustainable development and building an ecological civilization is imperative for the optimization of land-use patterns Sfakianaki (2015) Examined the impact of material reuse on sustainable construction to identify its importance and current thinking of the concept Smol et al (2015) The authors affirmed that the construction industry will benefit both economically and environmentally in the efficient use of waste such as sewage sludge Wang et al (2015) The authors found that eco-efficiency indicators are essential for ecological province construction as the pre-set indicators are inadequate Chang et al (2016) The authors identify strengthening technology innovation, improving standards and evaluation, establishing demonstration projects and publicity are the key supporting activities for sustainable construction Geldermans (2016) Result shows that circularity-values emerge at the intersection of specific intrinsic properties (material and product characteristics) and relational properties (building design and use characteristics), whilst combining multiple parameters for reusable materials Tong and Tao (2016) It is imperative to foster collaborative initiatives at the community level to build an inclusive space for recycling activities and promote waste management Esa et al (2017) Proposed a waste management ...…”
Section: Systematic Review Of Circular Economy Researchmentioning
confidence: 99%
“…• Tourism [10][11][12]; • Animal husbandry [13][14][15]; • Decommissioned school facilities [16] and churches [17] or manufacturing facilities [18], for example mills [19] and dams [20]; • Construction and management of new agricultural villages, especially in China [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…; Hong et al. ). Strict conservation of ecological‐function‐oriented and spatially explicit redline areas is one of the core components of a new environmental policy tool aimed at improving nature conservation and environmental protection (Jin & Lin ).…”
Section: Introductionmentioning
confidence: 98%